Intellectual Capital as Part of the Quality Management System in an Auditing Firm - LUBENCHENKOО. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2023)
A new approach to quality assurance in audit requires creating a quality management system that would include eight components: procedure for risk assessment in a firm; management and leadership; respective ethical norms; acceptance and continuations of relations with clients and specific engagements; engagement completion; resources; information and communication; the process of monitoring and correction. Each component requires a separate assessment in the monitoring of the quality management system, both at firm and engagement level. The article demonstrates that the component “Resources” (human, technological, intellectual) of the quality management system in an auditing firm can be considered from the management viewpoint as intellectual capital, thus making applicable recognized management models. By summing up research results produced by domestic and foreign scientists it was demonstrated that the model of European Foundation for Quality Management (EFQM model) can be applied in assessing the components of the quality management system, “Resources” in particular. EFQM model was adapted and extended in an elaborated working document for internal or external monitoring of the quality management system in an auditing firm. The working document includes performing of the following procedures: inspection (review) of documents and observations; individual interviews of the engaged firm staff; analysis of obtained evidence. The implementation and documenting of monitoring procedures and informing the results to all the firm staff will help assure the quality of auditing services and increase the users’ trust in the audit.